Informal influence processes in teams and organizations - Hohmann, Sebastian; Justus Liebig University Giessen (My University, 2019)
The purpose of this dissertation was to address important, yet largely neglected issues in our academic understanding of the development of informal influence behaviors in teams and organizations and, thus, to extend existing knowledge on the origins of these important behaviors. Using various research designs and methods, I examined contextual antecedents of a range of influence behaviors between coworkers across three independent studies, each with a unique research focus and drawing from different samples and contexts. In doing so, I aimed to address key ambiguities and oversights in the literatures on influence tactics and impression management strategies as well as informal leadership and, thus, to increase our academic understanding of lateral influence processes. In particular, Chapter 2 provided fresh insights into the behavioral consequences associated with individuals status in groups, illustrating why and when a perceived lack of status may trigger specific influence behaviors. Chapter 3 demonstrated both how and under what conditions supervisors formal task-oriented leadership may relate with an individual team member s respective behavior and, thus, with the member s emergence as an informal leader. Finally, Chapter 4 s findings illustrated how (conflicting) time pressure perceptions matter for the decision to engage in specific influence behaviors in collaborative work settings. All in all, this dissertation offers new knowledge on key contextual factors that may affect influence processes and behaviors between peers in teams and organizations. As such, it advances existing theory and practice in the field of organizational behavior by examining informal influence from various theoretical and empirical perspectives.
Keywords: ddc:330